Aplicação das técnicas espectroscópicas de RMN e IV e de métodos quimiométricos na quimiotaxonomia de liquens - Alcantara, Glaucia Braz (2007)
This present work describes the chemotaxonomic analysis of lichens through the utilization of NMR spectroscopic techniques, HR-MAS and NMR in solution, and IR allied with chemometrics methods. This analysis were carried out with eleven species set of lichens divided in two families and six genera. The HR-MAS NMR spectra together the chemometric, obtained from intact vegetal material, present the discrimination between the families, genera and species and the classification percentage was much satisfactory (70,8%). The analyzed substances include the carbohydrates class of low molecular-weight, the polyols. The NMR in solution analysis, corresponding to crude extracts, present the discrimination between genera and species and the classification was excellent (88,9%). In this analysis, where the secondary metabolites of lichens are evaluated, was realized the identification of some substances in mixture. The analysis by infrared spectroscopy (IR), also obtained from intact material, was detached by the excellent power of samples classification (100% of correct prediction), with discrimination between genera and species. The comparative application of this techniques confirm the results obtained separately, and point for a great potentiality of IR in chemotaxonomic analysis of lichens, due its quickness and low price, however the NMR techniques are more attractive when desire the circumstantial analysis of spectral profile.